Will the Requirement by the US FDA to Simultaneously Co-Develop Companion Diagnostics (CDx) Delay the Approval of Receptor Tyrosine Kinase Inhibitors for RTK-Rearranged (ROS1-, RET-, AXL-, PDGFR-α-, NTRK1-) Non-Small Cell Lung Cancer Globally? - Ou, Sai-Hong I. (Frontiers in Oncology, 2014)
The discovery of anaplastic lymphoma kinase (ALK) rearrangement in non-small cell lung cancer (NSCLC) in 2007 and the approval of crizotinib for the treatment of advanced ALK-rearranged NSCLC in 2011 represents a landmark in the development of targeted oncology therapy. The approval of crizotinib was accompanied simultaneously by the approval of approval of the Vysis (Abbott Molecular) break-apart fluorescence in situ hybridization test as the companion diagnostic (CDx) test to detect ALK rearrangement. Pfizer, the manufacturer of crizotinib, sponsored the screening of thousands of patients and the standardization of the ALK FISH test as part of the approval process for crizotinib, a first in class ALK inhibitor. Many pharmaceutical companies are now using the FDA-approved ALK FISH assay to enroll patients onto trials for their own respective ALK inhibitors. In essence they are “piggybacking” on the FDA-approved ALK FISH assay without having to pay for the development of a CDx, nor screening for ALK-rearranged NSCLC patients in the protocols because screening for ALK rearrangement is now the standard of care in NSCLC after the approval of crizotinib. Since 2007, rearrangement in more RTKs such as ROS1, RET, AXL, PDGFR-α, and NTRK1 have been discovered in NSCLC but the incidence of each subtype of RTK-rearranged NSCLC is quite rare. Crizotinib has now demonstrated significant clinical activity in ROS1-rearranged NSCLC patients. Whether crizotinib will gain official FDA approval for use in ROS1-rearranged NSCLC, on the other hand, remains unclear as there is no test for ROS1 rearrangement currently being developed to support US FDA approval as a CDx. This may be due in part to the fact that the full cost associated with the development of a pre-market approved (PMA)-approved CDx must be borne by the company seeking the first drug approval in a new indication. Given the low incidence of ROS1 rearrangement in NSCLC, and the availability of crizotinib in most countries